2001
DOI: 10.1021/jp010777u
|View full text |Cite
|
Sign up to set email alerts
|

Interference Microscopy Investigation of the Influence of Regular Intergrowth Effects in MFI-Type Zeolites on Molecular Uptake

Abstract: Interference microscopy is applied to carry out investigations of the influence of the regular intergrowth effects commonly observed in large silicalite-1 crystals on adsorption/desorption of isobutane. The intracrystalline concentration profiles measured by interference microscopy during adsorption of isobutane are compared with those simulated using the Monte Carlo method. The comparison of the simulated and the measured profiles allows the possibility that the uptake of isobutane from the gas phase into sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 15 publications
6
83
0
7
Order By: Relevance
“…Unfortunately, they do not provide any information on the temporal evolution of internal concentration profiles. A powerful method, explored Kärger and coworkers, [41][42][43][44] to reveal space-and time-resolved details, is interference microscopy. This technique is based on the principle that the optical density of an individual zeolite crystallite depends on the concentration and nature of the guest molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, they do not provide any information on the temporal evolution of internal concentration profiles. A powerful method, explored Kärger and coworkers, [41][42][43][44] to reveal space-and time-resolved details, is interference microscopy. This technique is based on the principle that the optical density of an individual zeolite crystallite depends on the concentration and nature of the guest molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the discrepancy at the higher temperature may not be attributed to the different length scales probed by PFG -NMR and MD. In previous studies [8,24] it was shown that no matter what the intracrystalline diffusivity is, a major contribution to the measured effective diffusivity must be expected from the inter-crystalline diffusivity, as well as from the fraction of molecules in the intercrystalline space around the crystallites; both quantities are highly temperature dependent.…”
Section: <Fig 7>mentioning
confidence: 99%
“…The IFM method has been successfully used to study micropore diffusion in a variety of zeolites such as ferrierite [6], CrAPO-5 and SAPO-5 [7][8][9][10] and MFI [11,12]. The measured concentration profiles in these systems have been used to determine whether the diffusion is one-dimensional, two-dimensional or three-dimensional.…”
Section: Introductionmentioning
confidence: 99%